Optimization Design and Feasibility Analysis of Electromagnetic Direct Drive Transmission - Yu Xiao; Ge Wenqing; LI Bo; Tan Cao; Jiang Xiaohan (Jixie chuandong)
A Direct-Driving Automated Mechanical Transmission （DAMT） for electric vehicles with integrated electromagnetic linear drive is proposes，and the shift performance is analyzed by simulation and experiment. The transmission combines the respective advantages of the direct drive technology and the mechanical transmission，and directly drives the two-speed integrated coupling sleeve to complete the shifting by using the electromagnetic linear driving device. In order to obtain the target of maximum shifting force and shifting force volatility，the parameters of the shifting actuator are optimized by the annealing particle swarm-finite element algorithm. The shifting mechanism of the electromagnetic direct drive transmission is studied for modeling and simulation of shift process in stages. The DAMT prototype and the test bench are built to perform the typical working condition shifting experiment. The experiment results show that under the condition of the electromagnetic direct-drive transmission with a speed difference of 220 r/min and a moment of inertia of the synchronous end of 0.04 kg<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m2，the shift time is 148 ms and the synchronization time is 109 ms. The modeling accuracy and the feasibility of the DAMT is verified by experimental result.